On Ti-18Si-6B and Ti-7.5Si-22.5B powder alloys prepared by high-energy ball milling and sintering - Fernandes, Bruno Bacci; Ramos, Alfeu Saraiva [UNESP]; Moura Neto, Carlos de; Coelho, Gilberto Carvalho; Suzuki, Paulo Atsushi (ABM, ABC, ABPol, 2012)
Recently, a new ternary phase was discovered in the Ti-Si-B system, located near the Ti6Si2B composition. The present study concerns the preparation of titanium alloys that contain such phase mixed with α-titanium and other intermetallic phases. High-purity powders were initially processed in a planetary ball-mill under argon atmosphere with Ti-18Si-6B and Ti-7.5Si-22.5B at. (%) initial compositions. Variation of parameters such as rotary speed, time, and ball diameters were adopted. The as-milled powders were pressureless sintered and hot pressed. Both the as-milled and sintered materials were characterized by X-ray diffraction, scanning electron microscopy and energy-dispersive spectrometry. Sintered samples have presented equilibrium structures formed mainly by the α-Ti+Ti6Si2B+Ti5Si3+TiB phases. Silicon and boron peaks disappear throughout the milling processes, as observed in the powder diffraction data. Furthermore, an iron contamination of up to 10 at. (%) is measured by X-ray spectroscopy analysis on some regions of the sintered samples. Density, hardness and tribological results for these two compositions are also presented here.
Keywords: multiphase intermetallics; phase identification; powder metallurgy